Voltage-Dependent Dopamine Potency at D1-Like Dopamine Receptors - Ågren, Richard; Sahlholm, Kristoffer (Frontiers in Pharmacology, 2020)
In recent years, transmembrane voltage has been found to modify agonist potencies at several G protein-coupled receptors (GPCRs). Whereas the voltage sensitivities of the Gαi/o-coupled dopamine D2-like receptors (D2R, D3R, D4R) have previously been investigated, the putative impact of transmembrane voltage on agonist potency at the mainly Gαs/olf-coupled dopamine D1-like receptors (D1R, D5R) has hitherto not been reported. Here, we assayed the potency of dopamine in activating G protein-coupled inward rectifier potassium (GIRK) channels co-expressed with D1R and D5R in Xenopus oocytes, at -80 mV and at 0 mV. Furthermore, GIRK response deactivation rates upon dopamine washout were measured to estimate dopamine dissociation rate (koff) constants. Depolarization from -80 to 0 mV was found to reduce dopamine potency by about 7-fold at both D1R and D5R. This potency reduction was accompanied by an increase in estimated dopamine koffs at both receptors. While the GIRK response elicited via D1R was insensitive to pertussis toxin (PTX), the response evoked via D5R was reduced by 64% (-80 mV) and 71% (0 mV) in the presence of PTX. Injection of oocytes with Gαs antisense oligonucleotide inhibited the D1R-mediated response by 62% (-80 mV) and 76% (0 mV) and abolished the D5R response when combined with PTX. Our results suggest that depolarization decreases dopamine affinity at D1R and D5R. The voltage-dependent affinities of dopamine at D1R and D5R may be relevant to the functions of these receptors in learning and memory.